Let's love ourselves : a little more each day! / Nur Ilianis Adnan - Adnan, Nur Ilianis (Academy of Language Studies, 2024)
Those who know me personally would know that I am such a huge fan of anything that has to do with ‘self-love’. If we don’t love ourselves, who would? Let’s love ourselves a little more each day because love holds so much power. Each individual gives and receives love in different ways. Hence, the definition of love varies from one person to another. In my opinion, loving myself means prioritising myself, taking good care of myself, and doing what I love. Now, ask yourself, how do you show love towards yourself? Recently, I found these tips on social media as I was scrolling. I quickly screenshotted and listed them down to check whether I can tick the list. You can try it too!